Training on Tummy Massage for Nasyiatul ‘Aisyiyah Cadres in East Purwokerto as an Effort to Improve the Quality of Life of Stunted Toddlers - Kusuma, Inggar Ratna; Dewi, Sawitri; Setiabudi, Ragil; Mustikawati, Irma Finurina (Edumedia Solution, 2025)
According to the 2022 Indonesian Nutritional Status Survey, the prevalence of stunting among children under five decreased to 21.6%, yet this figure remains above the national target of 14% and the **WHO threshold of 20%. Children in rural areas are more vulnerable to stunting due to limited access to healthcare, inadequate parental knowledge of nutrition, poor access to nutritious food, and insufficient clean water and sanitation facilities. In East Purwokerto Subdistrict, there are 1,955 toddlers, most of whom are at risk of stunting. The Tummy Massage Training was implemented to enhance the capacity of Aisyiyah cadres in stimulating toddlers’ growth and development, providing early management for gastrointestinal issues (such as bloating, constipation, and colic), and assisting in early stunting detection. The program involved 25 Nasyiatul ‘Aisyiyah cadres through counseling sessions and hands-on training. Pre-tests and post-tests were conducted to measure knowledge improvement, showing a notable increase of around 90%. After practical demonstrations, cadres were able to perform tummy massage effectively on toddlers. This community-based intervention proved effective in improving cadres knowledge and skills in managing gastrointestinal disturbances and supporting early stunting prevention efforts. The activity highlights the importance of empowering local health volunteers through practical training as a sustainable strategy to improve child health and reduce stunting rates in vulnerable communities.